Delivering Clinically on Our Knowledge of Oxytocin and Sensory Stimulation: The Potential of Infant Carrying in Primary Prevention - Norholt, Henrik (Frontiers in Psychology, 2021)
Oxytocin (OT) is one of the most intensively researched neuropeptides during the three past decades. In benign social contexts, OT exerts a range of desirable socioemotional, stress-reducing and immunoregulatory effects in mammals and humans and influence mammalian parenting. Consequentially, research in potential pharmacological applications of OT towards human social deficits/disorders and physical illness has increased substantially. Regrettably, the results from the administration of exogenous OT are still relatively inconclusive. Research in rodent maternal developmental programming has demonstrated the susceptibility of offspring endogenous OT systems to maternal somatosensory stimulation, with consequences for behavioral, epigenetic, cognitive and neurological outcomes. A translation of this animal research into practically feasible human parenting recommendations has yet to happen, despite the significant prevention potential implied by the maternal developmental programming research. Extended physical contact with full-term healthy infants in the months following birth might constitute the human equivalent of those specific rodent maternal behaviors, found to positively influence emerging OT systems. Findings from both OT and maternal programming research parallel those found for infants exposed to such extended parental physical contact, whether through skin-to-skin contact or infant carrying. Clinical support of parents to engage in extended physical contact represents a feasible intervention to create optimum conditions for the development of infant OT systems, with potential beneficial long-term health effects.